Evaluation and Activation of Cambalpur Bentonite for Industrial Utilization: Activation of Cambalpur Bentonite - Nasreen, Shagufta; Ghani, Abdul; Noor, Sohail (Biological Sciences - PJSIR, 2010)
An experimental study of the bentonite clays of Cambalpur (Attock) area of Pakistan, indicated their performance to be comparable with the imported clays and that these can be used as import substitute after activation by hydrochloric acid or sulphuric acid. No reversal of colour or adverse effects were noticed.